Chirality assignment for metallic species via coherent phonon oscillations in arc-discharge single-walled carbon nanotubes - Shin, Seong-Il; Lim, Yong-Sik; Kim, Myung Jong (KOREAN PHYSICAL SOC, 2015)
We performed transient absorption measurements with sub-10-fs pulses to observe coherent phonon (CP) oscillations of species in a micelle-suspended arc-discharge single-walled carbon nanotube (SWNT) ensemble. We applied a spectral-resolved measurement scheme to investigate the photon-wavelength dependence of CP oscillations of the radial breathing mode (RBM) specific to each species, covering a broad photon wavelength range from 700 to 1000 nm (1.771 - 1.240 eV). With a linear prediction singular value decomposition (LPSVD) method as a robust alternative for resolving closely-overlapped vibration modes, we divided multiple RBM peaks into two components, the M (11)-excited metallic species and the S (22)-excited semiconducting species, respectively. We resolved the RBM peaks into 22 metallic and 29 semiconducting species. Resolved metallic tubes showed a wide distribution in diameters from 1.3 to 2.3 nm, forming a chirality distribution from (2n + m) = 33 family to 51 family.
Keywords: GENERATION